How a single receptor-like kinase exerts diverse roles: lessons from FERONIA - Wang, Gaopeng; Zhao, Zhifang; Zheng, Xinhang; Shan, Wenfeng; Fan, Jiangbo (Molecular horticulture, 2022)
FERONIA (FER) is a member of the Catharanthus roseus receptor-like kinase 1-like (CrRLK1L) protein subfamily, which participates in reproduction, abiotic stress, biotic stress, cell growth, hormone response, and other molecular mechanisms of plants. However, the mechanism by which a single RLK is capable of mediating multiple signals and activating multiple cellular responses remains unclear. Here, we summarize research progress revealing the spatial–temporal expression of FER, along with its co-receptors and ligands determined the function of FER signaling pathway in multiple organs. The specificity of the FER signaling pathway is proposed to operate under a four-layered mechanism: (1) Spatial–temporal expression of FER, co-receptors, and ligands specify diverse functions, (2) Specific ligands or ligand combinations trigger variable FER signaling pathways, (3) Diverse co-receptors confer diverse FER perception and response modes, and (4) Unique downstream components that modify FER signaling and responses. Moreover, the regulation mechanism of the signaling pathway- appears to depend on the interaction among the ligands, RLK receptors, co-receptors, and downstream components, which may be a general mechanism of RLKs to maintain signal specificity. This review will provide a insight into understanding the specificity determination of RLKs signaling in both model and horticultural crops.